PERAN INVESTASI SYARIAH DALAM MENDORONG PERTUMBUHAN EKONOMI INDONESIA - Ramadhan, Bintang; Safira Damayanti; Safitri Damayanti; Dwi Hadi Suarno; Abu Rohmat (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Islamic investment has become a strategic instrument in Indonesia's economic development, not only as a means of fundraising but also as a driver of inclusive and sustainable growth. This study aims to analyze the role of Islamic investment in encouraging Indonesia's economic growth, focusing on its contribution to national economic stability and fiscal sustainability. The research uses a descriptive qualitative approach with an in-depth literature study method on secondary data from the Financial Services Authority (OJK), the Central Statistics Agency (BPS), and recent scientific publications. The results show that Islamic investment, through instruments such as sukuk (SBSN), Islamic stocks, and Islamic mutual funds, contributes significantly to infrastructure development financing, increased financial inclusion, and stabilization of the financial system. The basic Sharia principles that avoid speculation (gharar) and usury create better resilience to economic shocks, thereby supporting macroeconomic stability. Furthermore, government project financing through Sovereign Islamic Securities (SBSN) provides an alternative financing solution that positively impacts fiscal sustainability by reducing reliance on conventional debt. These findings confirm the importance of strengthening the Islamic investment ecosystem through education, product innovation, and supportive regulations to maximize its contribution in accelerating Indonesia's economic growth.Islamic investment has become a strategic instrument in Indonesia's economic development, not only as a means of fundraising but also as a driver of inclusive and sustainable growth. This study aims to analyze the role of Islamic investment in encouraging Indonesia's economic growth, focusing on its contribution to national economic stability and fiscal sustainability. The research uses a descriptive qualitative approach with an in-depth literature study method on secondary data from the Financial Services Authority (OJK), the Central Statistics Agency (BPS), and recent scientific publications. The results show that Islamic investment, through instruments such as sukuk (SBSN), Islamic stocks, and Islamic mutual funds, contributes significantly to infrastructure development financing, increased financial inclusion, and stabilization of the financial system. The basic Sharia principles that avoid speculation (gharar) and usury create better resilience to economic shocks, thereby supporting macroeconomic stability. Furthermore, government project financing through Sovereign Islamic Securities (SBSN) provides an alternative financing solution that positively impacts fiscal sustainability by reducing reliance on conventional debt. These findings confirm the importance of strengthening the Islamic investment ecosystem through education, product innovation, and supportive regulations to maximize its contribution in accelerating Indonesia's economic growth.